Building intelligent databases with Oracle PL/SQL, triggers, and stored procedure - Owens, Kevin T. (Prentice Hall PTR, 1996)
This text shows how to develop business applications, such as payroll or accounting software, using Oracle's version of SQL (Structured Query Language), triggers and stored procedures. It supports version 7.1 and illustrates through examples how to create and optimize applications using Oracle Triggers and stored procedure language. The accompanying disk has the source code samples found in the book.